Manajemen Pembelajaran dari Rumah dengan Menggunakan Media Video Pembelajaran dan Quizizz Pada Siswa Kelas VI SD N Karangasem 1 - Sofiyati Sofiyati; Suad Suad; Sri Surachmi (Jurnal Prakarsa Paedagogia, 2021)
The objectives of this study were to analyze and describe how the learning planning, actuating and evaluation at home in grade VI SD Negeri Karangasem 1, Sayung District, Demak Regency. This research uses a qualitative approach with the type of case study research. Research data collection techniques are: (1) observation, (2) in-depth interviews, and (3) documentation. To check the validity of the data, a credibility test was used in the form of triangulation of sources, triangulation of methods and reference materials. The data analysis techniques used were: (1) data reduction (data reduction), (2) data presentation (data display), and (3) conclusion drawing (conclusion drawing). The results showed that learning planning was in the form of: (1) making a lesson plan, (2) setting learning objectives, (3) preparing teaching materials, (4) determining learning strategies or methods, and 5) preparing learning facilities. In the implementation of learning related to: (1) teacher activities in learning, (2) student activities in the learning process, (3) teacher interactions with students. In teaching evaluation, many things need to be considered, including: (1) achievement of learning objectives, (2) effectiveness of the media used, (3) teacher and student responses, and d. problems and solutions.